2016
DOI: 10.18632/oncotarget.11768
|View full text |Cite
|
Sign up to set email alerts
|

Combining radiomic features with a miRNA classifier may improve prediction of malignant pathology for pancreatic intraductal papillary mucinous neoplasms

Abstract: Intraductal papillary mucinous neoplasms (IPMNs) are pancreatic cancer precursors incidentally discovered by cross-sectional imaging. Consensus guidelines for IPMN management rely on standard radiologic features to predict pathology, but they lack accuracy. Using a retrospective cohort of 38 surgically-resected, pathologically-confirmed IPMNs (20 benign; 18 malignant) with preoperative computed tomography (CT) images and matched plasma-based ‘miRNA genomic classifier (MGC)’ data, we determined whether quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 47 publications
1
68
0
2
Order By: Relevance
“…The field of radiomics aims to develop decision support tools. Therefore, it involves combining radiomics data with other patient characteristics, as available, to increase the power of the decision support models (17,34). We showed that radiomics features complemented the TNM staging system, helping to provide better prognostic ability for pretreatment PFS.…”
Section: Discussionmentioning
confidence: 98%
“…The field of radiomics aims to develop decision support tools. Therefore, it involves combining radiomics data with other patient characteristics, as available, to increase the power of the decision support models (17,34). We showed that radiomics features complemented the TNM staging system, helping to provide better prognostic ability for pretreatment PFS.…”
Section: Discussionmentioning
confidence: 98%
“…External validation in a large, independent data set is warranted. Furthermore, with a larger sample size, multivariable modeling and receiver characteristic curve analyses will be helpful to determine the utility of gender-specific radiologic measures of abdominal obesity in discriminating malignant from benign IPMNs, independent of and in combination with novel molecular and radiologic markers 19,20 , standard clinical and radiologic features encompassed by consensus guidelines 12 , and BMI. …”
Section: Discussionmentioning
confidence: 99%
“…The study population included a fixed cohort of 37 patients with IPMNs whose pre-operative CT images had recently been evaluated as part of a different study 20 . The cases had initially been identified using a prospectively maintained clinical database of individuals who underwent a pancreatic resection for an IPMN between 2006 and 2011 at Moffitt Cancer Center and Research Institute (Moffitt) and provided written consent for medical images and clinical data to be donated for research through protocols approved by the Institutional Review Board (IRB) of the University of South Florida, including Total Cancer Care 41 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations